2001
DOI: 10.1074/jbc.m102376200
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-dependent Recruitment of Phosphoinositide 3-Kinase to the Membrane by β-Adrenergic Receptor Kinase 1

Abstract: Agonist-dependent desensitization of the ␤-adrenergic receptor requires translocation and activation of the ␤-adrenergic receptor kinase1 by liberated G␤␥ subunits. Subsequent internalization of agonist-occupied receptors occurs as a result of the binding of ␤-arrestin to the phosphorylated receptor followed by interaction with the AP2 adaptor and clathrin proteins. Receptor internalization is known to require D-3 phosphoinositides that are generated by the action of phosphoinositide 3-kinase. Phosphoinositide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
170
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(180 citation statements)
references
References 35 publications
7
170
3
Order By: Relevance
“…The discrepancy is most likely due to the different β 2 AR expression methods used. Our study was performed in stably transfected HEK293 cells, which have a much higher initial rate of β 2 AR endocytosis and higher coupling efficiencies than the transiently transfected HEK293 cell systems utilized in the other studies [43]. Furthermore, we observed the same results on endocytosis using an independently derived stably transfected line of HEK293 cells (data not shown).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The discrepancy is most likely due to the different β 2 AR expression methods used. Our study was performed in stably transfected HEK293 cells, which have a much higher initial rate of β 2 AR endocytosis and higher coupling efficiencies than the transiently transfected HEK293 cell systems utilized in the other studies [43]. Furthermore, we observed the same results on endocytosis using an independently derived stably transfected line of HEK293 cells (data not shown).…”
Section: Discussionsupporting
confidence: 64%
“…This is consistent with other studies where the endocytosis of transferrin receptors [14,15], β 2 ARs [42] and AT1 angiotensin receptors [18] were measured in the presence of concentrations of wortmannin low enough to prevent nonspecific effects. Other studies have suggested that wortmannin inhibits agonist-induced β 2 AR endocytosis, and that agonistdependent recruitment of a PI 3-kinase to the plasma membrane is important for this process [43]. The discrepancy is most likely due to the different β 2 AR expression methods used.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, EP 4 receptors undergo rapid, PGE 2 -mediated desensitization (14) and internalization (15); whereas EP 2 receptors do not. Since the internalization of some G-protein-coupled receptors is associated with a transactivation of the MAPK pathway (16,17), it may be supposed that such a mechanism could explain the present findings of selective activation of ERK signaling by the EP 4 receptors. However, in a previous study using human EP 4 receptors expressed in HEK-293 cells, it was found that the phosphorylation of ERKs 1 and 2 was independent of PGE 2 -mediated receptor internalization (18).…”
Section: Induction Of Egr-1 Expression In Ep 4 -Expressing Cells Leadmentioning
confidence: 67%
“…To date, the specific cellular function that is associated with GRKs is GPCR phosphorylation and desensitization; recent findings unveil that GRKs are able to interact with nonreceptor proteins (PI3K, AKT, and MEK), suggesting new cellular functions for these kinases (16,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%